EFFICACY OF RITRIL APPLIED AGAINST HELMITHOSIS IN CATTLE - E. N. GLASYEV; I. A. ARKHIPOV; A. V. BALYSHEV; N. N. ZHUKOVA; O. S. DRAGUNKINA (Российский паразитологический журнал)
Efficacy of the injective anthelmintic drug Ritril produced on the base of Ricobendazole and Triclabendazole used in treatment of different types of helminthosis in cattle has been studied. It was determined that Ritril has a high anthelmintic efficacy when administered at a dose of 0,8 ml/10 kg of body weight. The drug shown a 100% efficacy in treatment of dictyocaulosis and strongylatosis of gastrointestinal tract. Fasciola spp. and Trichocephala spp. were more resistant to the effect of Ritril. Therefore it is recommended to use the drug at a higher dose – 1,6 ml/10 kg of body weight.